Świadomy i nieświadomy przekaz na temat kultury korporacyjnej w poradnikach redagowania korespondencji handlowej w języku francuskim - Elżbieta Gajewska (Ksiegarnia Akademicka Publishing, 2020)
A Conscious and Unconscious Message about Corporate Culture in the Guides for Editing Commercial Correspondence in French